Sorghum and millets diseases - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Sorghum and millets diseases: a second world review edited by W A J de Milliano R A Frederiksen and G D Bengston 1992 370p ISBN 92 9066 201 8 Pbk produced by lCRISAT, Patancheru Andhra Pradesh 502 324, INDIA